PENERAPAN MODEL KOOPERATIF TGT UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DAN HASIL BELAJAR IPS KELAS VIII E SMPN 1 RANDUDONGKAL - Putra, Hafidz Ady (IJTIMAIYA: Journal of Social Science and Teaching, 2019)
This research aims: (1) to improve social skill and learning outcomes of social studies of the eighth graders exactly Class E of SMPN 1 Randudongkal using TGT cooperative learning model with variations of the game. This research is Classroom Action Research that uses the model of Kemmis and Taggart. The Techniques of Collecting data used observation, interviews, test, field notes and documentation. The result of the research indicated an improvement of social skills and learning outcomes in social studies after the writer applied cooperative learning model TGT with variations of the game. The writer can proved there is the improvement of social skills. Before the action was done, the average of social skills was 46.88, after Cycle 1, there was the improvement in 72.66, in the end of Cycle 2, the average of social skills became 80.78. The improvement of the students’ learning outcomes can also be proved by the classical completeness percentage. The classical completeness percentage was 40.62% before the action. It was be 78.12% in the end of Cycle 1 and in the end of Cycle 2 improved to become 87.50%.